Penerapan Data Mining Klasifikasi Tingkat Pemahaman Siswa Pada Kegiatan Belajar Mengajar dengan Metode Decision Tree (Studi Kasus SDN Malaka Jaya 11 Duren Sawit) - Lestari, Dwi; Lestari, Sri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Very advanced technological developments can help all aspects of life, one of which is the world of education. The world of education certainly really needs the role of technology in managing activities by utilizing information technology. Problems arise in the system for processing piles of data to find out whether or not students are able to follow subjects at SDN Malaka Jaya 11. The process of implementing this data mining application alone discusses predicting children's ability levels in taking subjects. The data used is data from 5th grade elementary school students for the last 1 year of the academic year (2022 - 2023) at SDN Malaka Jaya 11. One classification model is to create a decision tree. By knowing the child's level of ability in following subjects, it is hoped that future solutions can be provided by students in processing student data with a computerized system, especially data regarding children's ability level in taking subjects. How the system built works using the decision tree method.